The Influence of Financial Attitude on Financial Management Behavior Mediated By Financial Literacy Of High School Students In Malang City - wati, Ratna; Rokhman, M. Taufiq Noor (Manajemen & Bisnis Jurnal, 2024)
Abstract. The purpose of this study is to determine and analyze the direct influence of financial attitudes on financial management behaviour, financial literacy and the direct influence of financial literacy on financial management behaviour. Knowing and analyzing financial literacy can mediate financial attitudes toward financial management behaviour. The population in this study were 305 students of Junior High School 14 Malang City, grade 9, with a sample size of 75 people. The analysis tool used was path analysis with a mediation test comparing the total effect to the direct effect. The results of the study explain that there is a significant influence of financial attitudes on financial management behaviour and financial literacy. Financial literacy has a direct and significant effect on financial management behaviour. Financial literacy can mediate the influence of financial attitudes on financial management behaviour. This study can contribute theoretically to the Planned Behavior Theory with the contribution of research results on the financial management behaviour of students at Junior High School 14 Malang City. Providing input to the management of Junior High School 14 Malang City on the importance of implementing good financial behaviour for students, by creating activity programs, and policies that are like applications for students of Junior High School 14 Malang City to wisely manage finances